Inactive Proteasomes Routed to Autophagic Turnover Are Confined within the Soluble Fraction of the Cell - Keren Friedman; Ofri Karmon; Uri Fridman; Yair Goldberg; Ophry Pines; Shay Ben-Aroya (Biomolecules, 2022)
Previous studies demonstrated that dysfunctional yeast proteasomes accumulate in the insoluble protein deposit (IPOD), described as the final deposition site for amyloidogenic insoluble proteins and that this compartment also mediates proteasome ubiquitination, a prerequisite for their targeted autophagy (proteaphagy). Here, we examined the solubility state of proteasomes subjected to autophagy as a result of their inactivation, or under nutrient starvation. In both cases, only soluble proteasomes could serve as a substrate to autophagy, suggesting a modified model whereby substrates for proteaphagy are dysfunctional proteasomes in their near-native soluble state, and not as previously believed, those sequestered at the IPOD. Furthermore, the insoluble fraction accumulating in the IPOD represents an alternative pathway, enabling the removal of inactive proteasomes that escaped proteaphagy when the system became saturated. Altogether, we suggest that the relocalization of proteasomes to soluble aggregates represents a general stage of proteasome recycling through autophagy.